El peso específico como un indicador de la calidad de semilla de arroz para la siembra - Gregori, Leonardo Agustin; Pirchi, Hector Javier; Arguissain, Gustavo Gabriel; Crepy, Maria Andrea (Sociedade Sul-Brasileira de Arroz Irrigado, 2023)
Poster